The Batasmiah Tradition in the Banjar Tribe Society of South Kalimantan - Vera Anggraini; Ketrin Segita; Rika Aulia; Novita Novita; Ronald Hadibowo Sangalang (CV. Rayyan Dwi Bharata, 2023)
Islam, Banjarese, is a strict character that can't be isolated from their identities.The emblematic signs of their religiousity apper as strict services related with the existence cycle , like marriage ,conceiving an offspring , and demise. Convictions that are well established locally make a ceremonies in culture obligatory to be done under standard regulation. The kind of examination utilized is as subjective exploration with information assortment methods of perception, meetings and documentation. Therefore culture is firmly connected with society. All that contained in the public not entirely set in stone by the way of life that is possessed by the local area itself. Culture is something passed down starting with one age then onto the next. With respect to Batasmiah custom, one might say that it is a mix of the way of life of the past precursors and the t eachings of the Islamic religion. This is surely not illegal. The service of naming an infant kid in the practice or culture of the Banjar public, South Kalimantan, is known as the Batasmiah. This restricting practice is gathered with the aqiqah occasion, some are done independently. The cutoff service is typically completed by the Banjar nation after the child is north of 40 days old or over a month by welcoming neighbors and family members and not segregating among young men and young ladies.